Pengaruh PDRB dan Inflasi Terhadap Tingkat Pengangguran Terbuka Dalam Perspektif Ekonomi Islam Di Kota Bengkulu Tahun 2015-2023 - Aditya Gusti Varizal; Asnaini; Rahmat Putra Ahmad Hasibuan (DPPM Universitas Pelita Bangsa, 2025)
This study aims to determine the effect of Gross Regional Domestic Product (GRDP) and inflation on the open unemployment rate in Bengkulu City from 2015 to 2023 with an Islamic economic perspective. The data used in this study are secondary data, namely quarterly data taken from the official website of the Bengkulu City Statistics Agency. The analysis techniques used in the quantitative approach are classical assumption tests, multiple linear regression tests and hypothesis tests and are assisted by software applications, namely IBM Statistics 2.20. and for the qualitative approach with the literature study method. The results of this study indicate that partially GRDP has a positive and insignificant effect and Inflation has a negative and insignificant effect on the Open Unemployment rate in Bengkulu City in 2015-2023. Simultaneously, GRDP and Inflation do not have a significant effect because they are not fully supported by various supporting factors. After that, with an Islamic economic perspective, it is revealed that the high unemployment rate and the discontinuity of wealth distribution reflect the suboptimal application of the values ​​of justice in Islam.